Provide and protect the essential components - Heidorn, B. (Journal of Physical Education, Recreation & Dance, 2020)
This article takes a look at the current educational climate during the worldwide COVID-19 pandemic, specifically the place that physical education has during this time. It explores the importance of maintaining standards-based learning and the essential components of physical education.